Cultivo de Crassostrea gigas (Bivalvia: Ostreidae) en una red semirigida - Acosta Ruíz, Manuel de J (1996)
A culture system, consistíng of a semi-rigid net, with an ABS frame filled with styrofoam was used for the culture of the Pacific oyster Crassostrea gigas, from 3.0 mm lenght seed. The culture system wa, tested in three ¡oeations, two inside San Quintín Bay and one in San Martín lsland. The mean monthly growth was 8.69 mm and 8.96 mm in the Bay and 7.33 mm in San Martín ¡sland. These growth rates show that this species can attain commercial sizes in 6 months, using the culture system tested.